Characterization of microscopic pore structures in Lower Silurian black shale(S1l), southeastern Chongqing, China. (March 2016) - Zhang, Qin; Liu, Renhe; Pang, Zhenglian; Lin, Wen; Bai, Wenhua; Wang, Hongyan
Abstract: Due to the large thickness and richness of organic matter in Longmaxi shale, southeastern Chongqing is considered as the most promising area for shale gas exploration and development and was a focus of numerous research interests in China. Characterization on the pore system of organic rich shale is significant for the reserve estimation and better understanding the production mechanism of shale gas plays. Shale composition, detected by X-ray diffraction, indicates that brittle minerals, especially quartz was the most prevalent component，with average contents of 41.72 wt.%. Pore types was classified by using a combination of argon-iron milling and field emission scanning electron microscopy (FESEM), and six types of pores were observed in rock images. High pressure mercury intrusion and low pressure N2 adsorption were performed to extract the pore size distribution of Longmaxi shale. The results show that the nanopore was the major pore type in shale samples, which accounts for 95.6% of the pore volume. In the nanopore system, pore with diameters between 2 nm and 10 nm is the major component that contributes 76% of the total pore volume and 78% of the whole inner surface area. Furthermore, the dominant pore shape was interpreted from the adsorption-desorption hysteresis loop shape, and the typical slit-shaped pores were identified in the examined shale samples. Based on single factor analysis method, organic matter richness is the main controlling factor for the volume of nanopore and the specific surface area. No direct correlation between brittle minerals and nanopores, but high quartz and calcite content makes it much easier for the formation to generate natural fractures and to be hydraulically fractured. The study can inspire and guide shale gas exploration and exploitation southeastern Chongqing to some extent. Highlights: Pore types were classified based on observation from FESEM images. Pore shape was determined from the hysteresis loops of N2 adsorption. Pore size distribution was obtained from mercury intrusion and N2 adsorption. Controlling factors for pore volume and BET surface area were discussed.